2008
DOI: 10.1021/ic801432b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Thermal Properties of Homoleptic Rare-Earth Guanidinates: Promising Precursors for MOCVD and ALD of Rare-Earth Oxide Thin Films

Abstract: Eight novel homoleptic tris-guanidinato complexes M[(N(i)Pr)(2)CNR(2)](3) [M = Y (a), Gd (b), Dy (c) and R = Me (1), Et (2), (i)Pr (3)] have been synthesized and characterized by NMR, CHN-analysis, mass spectrometry and infrared spectroscopy. Single crystal structure analysis revealed that all the compounds are monomers with the rare-earth metal center coordinated to six nitrogen atoms of the three chelating guanidinato ligands in a distorted trigonal prism geometry. With the use of TGA/DTA and isothermal TGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 56 publications
6
79
0
Order By: Relevance
“…270°C) of compound 1, according to the TG experiment. 27 The rapid decrease in GPC beyond 300°C is probably due to either re-evaporation of the chemisorbed precursor species, dehydroxylation of the film surface, or reduction of the precursor flux owing to self-decomposition before it reaches the substrate surface. 30−32 Similar growth behavior has been previously observed for ALD of RE oxide (e.g., Sc 2 O 3 growth utilizing [Sc(Cp) 3 ]/H 2 O).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…270°C) of compound 1, according to the TG experiment. 27 The rapid decrease in GPC beyond 300°C is probably due to either re-evaporation of the chemisorbed precursor species, dehydroxylation of the film surface, or reduction of the precursor flux owing to self-decomposition before it reaches the substrate surface. 30−32 Similar growth behavior has been previously observed for ALD of RE oxide (e.g., Sc 2 O 3 growth utilizing [Sc(Cp) 3 ]/H 2 O).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…25,26 It has also been shown that these ligands offer necessary reactivity, volatility, and good thermal stability, which are essential for an ALD precursor. 27 H 2 O assisted ALD of Gd 2 O 3 thin films using tris(N,N′-diisopropyl-2-dimethylamido-guanidinato) gadolinium(III) [Gd(DPDMG) 3 ] with preliminary results on the characterization of the ALD grown films were published as a communication earlier. 28 The current work demonstrates that the thin films of Gd 2 O 3 and Dy 2 O 3 can be grown efficiently by ALD using guanidinate based complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[31] The overlapping ALD window for HfO 2 and Gd 2 O 3 should enable the development of a truly waterbased ALD process for rare-earth (e.g., Gd, Dy) doped HfO 2 using the similar class of precursors. [32] This could be an added advantage for the optimization of the ALD process to grow high dielectric constant HfO 2 thin films in the cubic or tetragonal phase. Research efforts in this direction are currently underway.…”
Section: Hfo 2 Film Characterizationmentioning
confidence: 99%